Характерные особенности «театральной»» темы в русских водевилях первой половины XIX века - Мусулевська, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is dedicated to the analysis of Russian vaudevilles about the actors of the first half of the XIX century. The problems and poetics of the works are characterized in the context of respect for the actor’s profession. The development of action was psychologically justified and caused not by random coincidences, but by the nature of the heroes.